Changes of gut flora and endotoxin in rats with D-galactosamine-induced acute liver failure - Li, Lan-Juan (World J Gastroenterol, 2004)
AIM: To investigate the changes of gut microflora and endotoxin levels in rats with acute liver failure (ALF) induced by D-galactosamine (GalN). METHODS: Flora and endotoxin levels in the jejunum, ileum and colon in normal rats (group A) and rats with GalN-induced ALF were determined at 24 h (group B) or 48 h (group C) after GalN injection, as well as the endotoxin level in portal venous blood (PVB) and right ventricle blood (RVB) were determined by chromogenic limulus amoebocyte assay. RESULTS: Intestinal (jejunum, ileum, colon) lactobacillus count was statistically reduced in group B compared with those in group A (3.4 ± 0.3 vs 4.9 ± 0.3, 6.1 ± 0.4 vs 8.0 ± 0.3, 8.1 ± 0.2 vs 9.3 ± 0.2, P < 0.001, P < 0.001 and P < 0.001 respectively) and recovered partially in the group C compared with those in the group B, whereas the count of Enterobacteriaceae in the jejunum, ileum and colon in group B was increased markedly compared with those in the group A (5.1 ± 0.3 vs 3.6 ± 0.2, 6.9 ± 0.5 vs 5.3 ± 0.3, 8.7 ± 0.2 vs 7.6 ± 0.1, P < 0.001, P < 0.05 and P < 0.05 respectively) and restored partially in the group C compared with those in the group B. The endotoxin level in ileum was increased in the group B compared with those in the group A (111.3 ± 22.8 vs 51.5 ± 8.9, P < 0.05). In addition, the endotoxin level in PVB was obviously increased in group B compared with that in the group A (76.8 ± 9.1 vs 40.6 ± 7.3, P < 0.01) and reduced to the baseline at 48 h (group C). CONCLUSION: Severely disturbed gut flora in rats with GalN-induced acute liver failure plays an important role in the elevation of endotoxin level in PVB.